Pengaruh Fraud Diamond dan Gonetheory Terhadap Academic Fraud - Silfani Neva; Firdaus Amyar; Hardini Lestiani Hernusa (Forum Dosen Indonesia, 2021)
This research examines the factors of pressure, opportunity, rationalization, ability, greed, need, and disclosure of academic fraud behavior in accounting students at Institute of Business and Informatics Kesatuan Bogor. This type of research is a quantitative study, using a questionnaire as a research instrument measured by a Likert scale. This study used a sample of 306 students who had already participated in filling out the questionnaire that the researcher had distributed in the form of a Google Form. The data analysis technique used is multiple linear regression analysis using the IBM SPSS version 25 software. The results of this study indicate that the opportunity and need factors affect the academic fraud of accounting students at the Bogor Institute of Business and Informatics, while the factors of pressure, rationalization, ability, greed, and disclosure have no effect on academic fraud committed by accounting students at the Institute of Business and Informatics Kesatuan.